Septic Arthritis of the Shoulder Complicating Pregnancy - Sara Raiser; Kathryn Davidson; Ashley Walsh; Robert Egerman (Case Reports in Obstetrics and Gynecology)
Septic arthropathy leads to rapid joint destruction, impairment, and disability. Staphylococcus can be particularly virulent to bone and joints leading to adverse obstetric events. At 28 of weeks gestation, a patient presented with pyelonephritis and progressive left shoulder pain. Magnetic resonance imaging indicated early clavicular destruction and acromial involvement. Glenohumeral joint aspiration produced Staphylococcus aureus. The patient then had premature rupture of membranes and progressed rapidly to preterm delivery. Placental pathology revealed chorioamnionitis and microabscesses. Treatment of the infected joint required further surgical drainage and bone resection as well as extended antibiotics. It is important to remember that joint pain in pregnancy may indicate infective arthritis, and pyelonephritis can be a source of such an infection. Evaluation includes magnetic resonance imaging and consultation for joint aspiration. Prompt recognition and treatment are necessary to prevent joint destruction.